2016
DOI: 10.1371/journal.pone.0167753
|View full text |Cite
|
Sign up to set email alerts
|

Association between Age and the 7 Repeat Allele of the Dopamine D4 Receptor Gene

Abstract: Longevity is in part (25%) inherited, and genetic studies aim to uncover allelic variants that play an important role in prolonging life span. Results to date confirm only a few gene variants associated with longevity, while others show inconsistent results. However, GWAS studies concentrate on single nucleotide polymorphisms, and there are only a handful of studies investigating variable number of tandem repeat variations related to longevity. Recently, Grady and colleagues (2013) reported a remarkable (66%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The results of the genetic analysis demonstrated no association between the presence of the 7 repeat allele in the DRD4 gene and higher cigarette consumption, or among those patients with a diagnosis of COPD secondary to smoking where nicotine addiction (evaluated by Fagerström test) was higher. The frequencies of the short (S) and long (L) alleles in the study population were similar to the rest of the populations previously reported in the literature [10,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 88%
“…The results of the genetic analysis demonstrated no association between the presence of the 7 repeat allele in the DRD4 gene and higher cigarette consumption, or among those patients with a diagnosis of COPD secondary to smoking where nicotine addiction (evaluated by Fagerström test) was higher. The frequencies of the short (S) and long (L) alleles in the study population were similar to the rest of the populations previously reported in the literature [10,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 88%
“…A negative association was also observed between human longevity and the presence of the minor variant G of the SNP rs6276, mainly when the allele is homozygous, and this is explained because said SNP causes the DRD2 mRNA to degrade more rapidly when enhance its binding to various miRNAs such as miR-485-5p (Crocco et al 2016 ). Meanwhile, a variable number tandem repeat (VNTR) has been reported in the third exon of the DRD4 gene and the seven-repeat allele was associated with increased levels of physical activity and longevity, preferably in women (Grady et al 2013 ; Szekely et al 2016 ).…”
Section: Gpcr Influencing Lifespanmentioning
confidence: 99%